Macroscopic and Microscopic Identification in Native Chicken (Gallus domesticus) Organ with Helminthiasis - Haryo, Albiruni; Ginting, Ivana Aginta Br; Oktavianie, Dyah Ayu (Universitas Airlangga, 2021)
The native chickens collected from the Blimbing Malang Market were found with a state of lethargy and diarrhea. Native chickens were dissected to find out pathological abnormalities that occurred in the chicken's body by carrying out physical examinations and histopathological examinations. Based on the results of observations and examinations carried out both macroscopically and microscopically after necropsy chickens, the organs of chickens that have pathological abnormalities are the duodenum, jejunum and pulmo. The duodenum and jejunum had nematode infestations which showed villi erosion, hemorrhage, liquefactive necrosis, and inflammatory cell infiltration. Pulmo had hemorrhagic parabronchii, atelectasis of blood capillaries, cloudy swelling, and congestion of blood vessels. The visible abnormality of the small intestine organ damage leads to chicken disease to nematode worm infestation.